2011
DOI: 10.1037/a0024150
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of stability in adult attachment: An empirical test of two models of continuity and change.

Abstract: One of the core assumptions of attachment theory is that attachment representations are stable over time. Unfortunately, the data on attachment stability have been ambiguous, and as a result, alternative theoretical perspectives have evolved to explain them. The objective of the present research was to evaluate alternative models of stability by studying adults in 2 intensive longitudinal investigations. Specifically, we assessed attachment representations in 1 sample (N ϭ 203) daily over a 30-day period and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
201
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(214 citation statements)
references
References 53 publications
9
201
0
4
Order By: Relevance
“…It tells that as they gain more experience, their intrinsic motivation diminishes and they will start using the technology only for its functionality and they might even start thinking of replacing their current devices with more novel devices which the most likely will once again increase their intrinsic motivation. This is supported by numerous studies that suggested that attachment is not stable over time and can be changed as time passes by (Fraley et al, 2011;Sadikaj et al, 2011 (Belk, 1988). This reasoning could also be related to users' social desirability (Crowne and Marlowe, 1964)].…”
Section: ⅴ Discussion and Limitationssupporting
confidence: 51%
“…It tells that as they gain more experience, their intrinsic motivation diminishes and they will start using the technology only for its functionality and they might even start thinking of replacing their current devices with more novel devices which the most likely will once again increase their intrinsic motivation. This is supported by numerous studies that suggested that attachment is not stable over time and can be changed as time passes by (Fraley et al, 2011;Sadikaj et al, 2011 (Belk, 1988). This reasoning could also be related to users' social desirability (Crowne and Marlowe, 1964)].…”
Section: ⅴ Discussion and Limitationssupporting
confidence: 51%
“…There is research demonstrating stability in attachment orientations throughout life (Collins & Read, 1994), as well as evidence showing that attachment orientations are to some degree changeable as they influence and are influenced by relationship experiences. Stated differently, the latter perspective implies that attachment orientations are subject to revision and updated in response to new relationship experiences (Birnbaum, Reis, Mikulincer, Gillath, & Opraz, 2006;Collins & Read, 1994;Fraley, Vicary, Brumbaugh, & Roisman, 2011).…”
Section: Ipv and Relational Well-beingmentioning
confidence: 99%
“…Traditionally, attachment orientations were approached as static personality characteristics that remain stable across relationships (Bowlby, 1969(Bowlby, /1982(Bowlby, , 1973. Currently, researchers take a more dynamic approach, stating that attachment is not simply a trait but might be influenced by relationship experiences (e.g., Fraley et al, 2011). As discussed by other researchers (e.g., Allison et al, 2008;Mikulincer & Shaver, 2007;Weston, 2008), our results suggest that insecure attachment orientations put people at risk to enter or remain in a violent relationship and/or that the involvement in a long-term violent relationship can trigger the development of insecure attachment orientations.…”
Section: Main Findings On Ipv Victims' Mental Relational and Sexualmentioning
confidence: 99%
“…Известно, что стиль привязанности к родителям оста-ется довольно стабильным на длитель-ных промежутках времени [24], однако в романтических отношениях взрослых он довольно изменчив [11], кроме того, наблюдаются различия в проявлении привязанности в различных отношениях [19]. Тем не менее, анализ динамики сти-ля привязанности в лонгитюдном иссле-довании позволил сделать вывод о том, что в основе стиля, скорее всего, лежит относительно стабильный «прототип», вокруг которого происходят ситуатив-ные колебания оценок [11].…”
Section: социальная психология и общество 2017 г том 8 №unclassified